Toll-like receptor 4 deletion partially protects mice from high fat diet-induced arterial stiffness despite perturbation to the gut microbiota - Ecton, Kayl E.; Graham, Elliot L.; Risk, Briana D.; Brown, Gabriele D.; Stark, Grace C.; Wei, Yuren; Trikha, S. Raj J.; Weir, Tiffany L.; Gentile, Christopher L. (Frontiers in Microbiomes, 2023)
The present study aimed to determine the effects of toll-like receptor 4 (TLR4) deletion on high fat diet-induced aortic stiffness and gut dysbiosis. We hypothesized that a high fat diet would cause gut dysbiosis in both control and TLR4 knockout mice (TLR4-/-), but the absence of TLR4 signaling would protect mice from the downstream vascular consequences of the high fat diet. Male control C57BL/6J mice (CON, n=12) and TLR4-/ - mice (KO, n=12) were fed either a standard low-fat diet (SD) or a high fat diet (HFD) (60% kcals from fat) for 6 months, after which time measurements of aortic stiffness (via pulse wave velocity [aPWV]) and gut microbiota composition (16S rRNA sequencing) were determined. Compared to the SD, HFD reduced microbial variability, prompted gut microbial dysbiosis, and increased intestinal permeability in both CON and KO mice, with no effect of genotype. This increased intestinal permeability in HFD mice was accompanied by increases in circulating lipopolysaccharide binding protein (LBP) levels, an indicator of circulating endotoxin (p<0.05 for all comparisons between HFD and SD groups). aPWV was increased in CON+HFD mice (CON+HFD vs CON+SD : 525.4 ± 16.5 cm/sec vs. 455.2 ± 16.5 cm/sec; p<0.05), whereas KO+HFD mice displayed partial protection from HFD-induced arterial stiffening (KO+HFD vs. CON+SD: 488.2 ± 16.6 cm/sec vs. 455.2 ± 16.5 cm/sec; p=0.8) (KO+HFD vs. CON+HFD: 488.2 ± 16.6 cm/sec vs. 525.4 ± 16.5 cm/sec; p=0.1). In summary, TLR4 KO mice are not protected from deleterious alterations in gut microbial composition or intestinal permeability following a HFD, but are partially protected from the downstream arterial stiffening, suggesting that TLR4 signaling is not required for HFD-mediated intestinal disturbances, but is an important determinant of downstream vascular consequences.